Don Giovanni dramma giocoso in two acts - Mozart, Wolfgang Amadeus 1756-1791 (Unitel GmbH & Co. KG, 2021)
"A Mozart drawn from historical sources and yet anchored in our own time."--Die Presse
Enthält Bonusmaterial: Nikolaus Harnoncourt - between obsession and perfection. Part 2. Don Giovanni
Interpreten unter anderem: Don Giovanni, Andrè Schuen ; Il commendatore, Masetto, Mika Kares ; Donna Anna, Christine Schäfer ; Don Ottavio, Mauro Peter ; Donna Elvira, Maite Beaumont ; Leporello, Ruben Drole ; Zerlina, Mari Eriksmoen ; Arnold Schoenberg Chor ; Erwin Ortner (Choreinstudierung) ; Concentus Musicus Wien ; Nikolaus Harnoncourt, Dirigent
Live-Aufnahme: Wien, Theater an der Wien, 2014
Bildformat: 16:9
Keywords: Operas; Opera films; Film; Blu-Ray-Disc